Cancer incidence in Krakow in 2004–2006 - Rachtan, Jadwiga; Sokołowski, Andrzej; Geleta, Małgorzata; Molong, Łucja; Widawska, Anna; Żmurko, Renata (Contemporary Oncology/Współczesna Onkologia, 2008)
This publication presents data on cancer incidence in Krakow in the years 2004-2006. Also cancer incidences in both sexes in the years 1994-1996 and 2004-2006 are compared. Incidence data are based on Reporting Cards sent to Małopolska Cancer Registry. There have been counted the average yearly number of new cases, crude rates and age-standardized rates. There were 9626 cancer cases registered in Krakow, 4492 in males and 5134 in females in the years 2004-2006. An average of 1497 new cases in males and 1711 in females were registered every year. The age-standardized cancer incidence in males was 278.3/100 000 and 236.4/100 000 in females. The percentage of histopathologically confirmed cancer diagnoses was 80.2% in males and 81.4% in females. The comparison of the most common cancer incidence in males in the years 1994-1996 and 2004-2006 revealed a significant increase in incidence rates of colorectal cancer (25.6/100 000 vs. 33.9/100 000, p=0.0435) and prostate cancer (16.4/100 000 vs. 33.2/100 000, p=0.0000); however, a significant decrease in incidence rates was observed for lung cancer (68.5/100 000 vs. 56.4/100 000, p=0.0422) and stomach cancer (22.1/100 000 vs. 13.2/100 000, p=0.0050). In the compared periods, there was observed significant improvement in the percentage of histopathologically confirmed cancer diagnoses.